2019
DOI: 10.3389/fphar.2019.00725
|View full text |Cite
|
Sign up to set email alerts
|

Trained Circulating Monocytes in Atherosclerosis: Ex Vivo Model Approach

Abstract: Inflammation is one of the key processes in the pathogenesis of atherosclerosis. Numerous studies are focused on the local inflammatory processes associated with atherosclerotic plaque initiation and progression. However, changes in the activation state of circulating monocytes, the main components of the innate immunity, may precede the local events. In this article, we discuss tolerance, which results in decreased ability of monocytes to be activated by pathogens and other stimuli, and training, the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In addition, changes in monocyte inflammatory activation may hinder the resolution of inflammation in atherosclerotic lesions and contribute to disease progression. [ 17 ] Canpolat et al showed that the monocyte count was significantly higher in the CSFP group than in the normal control group. [ 4 ] Our findings are consistent with those of earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, changes in monocyte inflammatory activation may hinder the resolution of inflammation in atherosclerotic lesions and contribute to disease progression. [ 17 ] Canpolat et al showed that the monocyte count was significantly higher in the CSFP group than in the normal control group. [ 4 ] Our findings are consistent with those of earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…Monocyte polarization plays a key role in the progression of various inflammatory diseases such as atherosclerosis, myocardial infarction, and diabetic cardiomyopathy [236][237][238]. Infiltrated monocyte differentiation depends on the tissue microenvironment they reside in and the external stimuli they receive [239].…”
Section: Bmp-7 Differentiates Monocytes Into M2 Macrophages In Heart mentioning
confidence: 99%
“…Using RNA-seq data (GSE41690), transcriptomic alterations in PBMs from periodontitis patients were compared with PBMs of periodontal healthy subjects [9]. In case of atherosclerosis, PBMs are reported to be in an activated state and respond more strongly against lipopolysaccharide (LPS) stimulation, showing the increased expression of inflammatory mediators [10]. A publicly available microarray dataset (GSE23746) pertains to transcriptomic aberrations occurring in the PBMs of atherosclerosis patients versus the systemically healthy subjects.…”
Section: Introductionmentioning
confidence: 99%